Pengaruh Tekanan Operasi Membran Dalam Pengolahan Air Limbah Pulp Dan Kertas - Eufransia, Lamria; Pinem, Jhon Armedi; Amri, Idral (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Membrane technology is an effective technology to purify wastewater. The objective of the research is to determine the performance of the ultrafiltration for removal of BOD5, COD and TSS from wastewater of pulp and paper industry. This research has been conducted on wastewater treatment of pulp and paper industry with ultrafiltration process using poly aluminium chloride as a coagulant. Wastewater purified by ultrafiltration membranes with a variation of operating pressure 1.0 bar; 2.0 bar; and 3,0 bar. The result show that ultrafiltration process removed 78,93% of BOD5; 84,22% of COD; and 88,64% of TSS with flux value of 65,95 L/m2.jam at 3,0 bar. Keywords: Pulp and paper wastewater, poly aluminum chloride,rejection, ultrafiltration